2000
DOI: 10.1099/00221287-146-7-1605
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the ClpATPase ClpA of Brucella suis, and persistence of a knockout mutant in BALB/c mice The GenBank accession number for the sequence reported in this paper is AJ224881.

Abstract: The protein ClpA belongs to a diverse group of polypeptides named ClpATPases, which are highly conserved, and which include several molecular chaperones. In this study the gene encoding the 91 kDa protein b-ClpA of the facultative intracellular pathogen Brucella suis, which showed 70 % identity to ClpA of Rhodobacter blasticus, was identified and sequenced. Following heterologous expression in Escherichia coli strains SG1126 (∆clpA) and SG1127 (∆lon ∆clpA), b-ClpA replaced the function of E. coli ClpA, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Statistical analysis showed that, based on the assumption that B. suis 1330 possesses Ϸ3,200 genes, the maximal probability to pick up a gene at least once was 96.5%. The resulting mutants were screened for their participation in virulence by infection of the macrophage cell line THP-1, as described (15,18), and by individual analysis of intracellular multiplication by using fluorescence microscopy, as described in Materials and Methods. The disrupted genes were identified by sequencing the chromosomal DNA flanking Tn5 and homology search by using BLAST. One hundred thirty-one mutants unable to multiply in THP-1 cells were selected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis showed that, based on the assumption that B. suis 1330 possesses Ϸ3,200 genes, the maximal probability to pick up a gene at least once was 96.5%. The resulting mutants were screened for their participation in virulence by infection of the macrophage cell line THP-1, as described (15,18), and by individual analysis of intracellular multiplication by using fluorescence microscopy, as described in Materials and Methods. The disrupted genes were identified by sequencing the chromosomal DNA flanking Tn5 and homology search by using BLAST. One hundred thirty-one mutants unable to multiply in THP-1 cells were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Wells containing attenuated mutants showed no intracellular fluorescence, allowing their rapid identification. Attenuation of the selected mutants was validated in THP-1 infection experiments performed in duplicates in 24-well plates where the number of intracellular bacteria was determined at 90 min and 7, 24, and 48 h postinfection (15).…”
Section: Screening Of B Suis Tn5 Mutants For Attenuation In Human Thmentioning
confidence: 99%
See 1 more Smart Citation
“…But for the absence of an O-PS linked to the remaining LPS molecule, it can be predicted that not all these mutants are equivalent and they can be hypothetically grouped as follows: (i), R mutants have a complete lipid A-core plus a cytoplasmic O-PS, the incorporation of which to the LPS is blocked (at least the wzm/wzt and possibly the WaaL mutants); (ii), R mutants have a complete lipid A-core but no O-PS (mutants in wb** glycosyltransferases, in wecA, and in genes coding for enzymes necessary to synthesise some precursors, such as manBOAg, gmd and per) and (iii), R mutants have progressive deficiencies in the core and that may or may not accumulate cytoplasmic O-PS (mutants in some wa** genes and in some precursor genes such as manBcore). Mutants of each of these three groups have in fact been described, and the question then arises as to what extent they are equivalent in attenuation and immunizing abilities (27,28,29,30). Numerous outer and inner membranes, cytoplasmic, and periplasmic antigenic proteins have also been characterized.…”
Section: Antigenic Compositionmentioning
confidence: 99%
“…In the construct containing the 3Ј half of clpB, a 400-bp EcoRV-Bsu15I fragment located within the open reading frame encoding ClpB was replaced by the kanamycin resistance gene from pUC4K. The whole insert was blunted and recloned into the Brucella suicide vector pCVD442 (3) prior to electroporation of B. suis (4). clpB inactivation by double recombination was confirmed by Southern blot analysis (not shown) and by Western blot using polyclonal anti-E. coli ClpB cross-reacting with the homologous protein of B. suis (Fig.…”
mentioning
confidence: 99%